Depression means different things: A qualitative study of psychiatrists' conceptualization of depression in the palliative care setting. Issue 5 (October 2015) - Ng, Felicity; Crawford, Gregory B.; Chur-Hansen, Anna
Abstract: Objective: Medical practitioners conceptualize depression in different ways, which adds to the challenges of its diagnosis and treatment, as well as research in the palliative care setting. Psychiatric assessment is often considered the "gold standard" for diagnosis, therefore how psychiatrists conceptualize depression in this setting is pertinent. Our study aimed to investigate this issue. Method: Psychiatrists working in palliative care in Australia were individually interviewed using a semistructured approach. Nine participants were interviewed to reach data saturation. Interview transcripts were analyzed for themes. Results: Three overarching themes were identified: (1) depression means different things; (2) depression is conceptualized using different models; and (3) depression is the same concept within and outside of the palliative care setting. Participants explicitly articulated the heterogeneous nature of depression and described a different breadths of concepts, ranging from a narrow construct of a depressive illness to a broader one that encompassed depressive symptoms and emotions. However, depressive illness was a consistent concept, and participants considered this in terms of phenotypic subtypes. Participants used three models (spectral, dichotomous, and mixed) to relate various depressive presentations. Significance of Results: Psychiatrists did not subscribe to a unitary model of depression but understood it as a heterogeneous concept comprised of depressive illness and other less clearly defined depressive presentations. Given the influence of psychiatric opinion in the area of depression, these findings may serve as a platform for further discussions to refine the concepts of depression in the palliative care setting, which in turn may improve diagnostic and treatment outcomes.